Knowledge, attitudes and practices analysis of farmers on the risk of introducing peste des petits ruminants from Angola into northern communal areas of Namibia - Crafford, Jan Ernst (University of Pretoria, 2024)
Dissertation (MSc (Global One Health: Diseases at the Human and Animal Interface))--University of Pretoria, 2023.